Prevalence of accessory navicular in Japanese children: A cross-sectional study using ultrasound–Katsuragi Integrated Defense for Locomotive Syndrome in children study - Takahide Sasaki; Masatoshi Teraguchi; Kanae Mure; Yoshiki Asai; Yusuke Kido; Makiko Onishi; Takashi Shimoe; Nobuyuki Miyai; Yukihiro Nakagawa; Hiroshi Hashizume; Hiroshi Yamada (PLoS ONE, 2025)
The accessory navicular (AN) is an accessory bone located on the posteromedial aspect of the navicular tuberosity that can cause pain following overuse or trauma, particularly during childhood. However, the detailed epidemiological characteristics of AN in children have not been well studied. This study aimed to clarify the prevalence of AN and painful AN among Japanese children by examining the characteristics according to sex and age. This cross-sectional study used data from the Katsuragi Integrated Defense for Locomotive Syndrome in Children Study, focusing on musculoskeletal disorders in 875 children aged 6–15 years, with 1750 feet being assessed. Children were divided into five age groups: 6–7, 8–9, 10–11, 12–13, and 14–15. AN was detected using ultrasound to avoid radiation exposure. The sex- and age-group-dependent prevalence of AN and painful AN were calculated, and statistical analyses examined sex differences in prevalence by age group. The overall prevalence of AN was 15.1%, higher in females (17.9%) than in males (12.3%). The prevalence of AN increased with age in both sexes. Among cases diagnosed with AN, 20.8% were symptomatic, with a unimodal peak observed at ages 12–13 in males and 10–11 in females. No statistically significant differences were observed in the proportion of painful AN between sexes. This is the first large-scale epidemiological study on AN in children. The overall prevalence of AN was 15.1%, higher in females than in males. Additionally, 20.8% of patients with AN experienced pain. The results of this study provide important epidemiological data to support clinical management strategies for pediatric patients with AN.